The effect of exercise and nutritional support on elderly and senile patients with sarcopenic obesity - I. E. Pleshchev; V. N. Nikolenko; E. E. Achkasov; Ya. I. Preobrazhenskiy; L. A. Gridin; A. N. Shkrebko; M. V. Tsoller (Acta Biomedica Scientifica)
The aim of the review. To analyze the prevalence of sarcopenic obesity among elderly and senile people, to assess its causes, and to present modern methods for its prevention and physical rehabilitation.This review article discusses the most recent evidence on age-related changes in fat and muscle tissue, and on calorie restriction and exercise that have positive effect on physical performance in older people with sarcopenic obesity. In addition, potential gaps in clinical practice guidelines that merit attention in future research are identified and analyzed.Search strategy. We used the following key words to define participation in the review:“sarcopenic obesity”, “sarcopenia with obesity”, “sarcopenia”, “elderly/old age”. Inclusion and exclusion criteria. The review included original research results (reviews, meta-analyses). Editorials, proceeding of the conferences, and research protocols were excluded. The study sample included women and men of any race aged ≥ 60 years with a diagnosis of sarcopenic obesity and with preserved locomotion function. Articles involving hospital patients were also excluded. Non-human studies and studies that did not report precise intervention criteria (e. g., nutrition, exercise, duration, etc.) were excluded.The literature search was conducted in four electronic databases: PubMed, Cochrane Library, Springer, Scopus, for the period from 2013 to August 1, 2023. There were no restrictions on the language of the publication.